Africapolis, une nouvelle géographie urbaine de l’Afrique - Confins (Confins)
Africa is expected to experience the fastest urban growth rate in the world until 2050. By this time, African cities are expected to host an additional 950 million inhabitants. This growth is largely taking place in small and medium-sized cities. The African urban transition brings great opportunities; it also poses significant challenges. African urban agglomerations most often develop without benefiting from policies or investments commensurate with these challenges. Urban planning and management are therefore priority development issues. Understanding urbanization, its drivers, its dynamics and its impacts is essential for designing policies - local, national and continental - that are targeted, inclusive and forward-looking. This report, based on the Africapolis geospatial database (www.africapolis.org) covering 7,600 urban agglomerations from 50 African countries, analyzes urban dynamics from historical, political and environmental angles. It covers all strata of the urban network - from small and intermediate cities to metropolises. It therefore offers more inclusive and targeted policy options that integrate the local, national and regional scales of urban development in line with African realities.